Anteroposterior Stability and Knee Strength after Anterior Cruciate Ligament Reconstruction in Patients Older than 50 Years Compared to Younger Patients - Wutphiriya-angkun, Sombun (Journal of Southeast Asian Orthopaedics, 2021)
Purpose: The treatment for anterior cruciate ligament injury in middle-aged people older than 50 years remains controversial. This retrospective study was conducted to test the hypothesis that clinical outcomes are similar in the two age groups for anterior cruciate ligament reconstruction. Methods: A total of 41 patients were included. Twenty patients older than 50 years and 21 younger than 40 years. Patient data collected included preoperative and postoperative range of motion, visual analog scale, Lysholm Knee Scoring, International Knee Documentation Committee Knee Evaluation Form scores, anterior drawer test, Lachman test and pivot-shift test. Results: There were no significant differences in postoperative range of motion, visual analog scale score, anterior drawer test, Lachman test and pivot-shift test. Lysholm score and International Knee Documentation Committee knee evaluation form score between the two groups were significantly better in the younger age than the older group. Conclusions: Anterior cruciate ligament reconstruction in younger patient is more effective comparable to patients older than 50 years in the treatment of anterior cruciate ligament tears.